Impedimetric determination of antiretroviral drugs on a modified glassy carbon electrode - Chihava, Ruvimbo; Moyo, Mambo; Shumba, Munyaradzi (Institute of Electrical and Electronics Engineers Inc., 2021)
An impedimetric sensor was fabricated for the determination of determination of lamivudine (LAM) and tenofivir disoproxil fumarate (TDF) using a modified glassy carbon electrode. The glassy carbon electrode was modified with nickel-cobalt sulfide decorated graphene quantum dots (Ni-CoS-GQDs). Characterization of the fabricated sensor was achieved by using UV-Vis, electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The LODs were 56.18 μg/ml, LAM and 56.13 μg/ml, TDF. The average recovery range was 98.85%.